PSYCHOSSOCIAL DETERMINANTS OF DOMESTIC CARE BY FAMILIESS MEMBERS OF PERSONS WHO LIVE WITH HIV/AIDS - Machado, Cíntia Yuri S. B.; Figueiredo, Marco Antonio C.; Souza, Lícia B. (Medicina (Ribeirao Preto), 2008)
The investment in training and counselling of laypeople involved in the care in HIV/aids has allowed the creation of parallel resources to the hospital attendance. The family can represent a source of resources to regulate hospitalization flow and to reduce the amount of time spent coping with the disease and its desruptive effects, determined by preconceptions of gender, sexuality, use of drugs and homosexuality. This research aimed at identifying, under the perspective of domestic caregivers, some elements of appropriation of effetive conditions for the maintenance of care of people with HIV/aids in the domestic environment. Half-structuralized interviews were carried with 4 domestic caregivers, their relatives with HIV/aids companions, in the clinic of the Special Unit of Treatment the Infectum-Contagious Illnesses from the Clinics Hospital of the Faculty of Medicine of Ribeirão Preto. The interviews had followed the procedures of evocation, articulation and verification of answers. Later, successive analyses of content, on the transcription of the interviews, had allowed the synthesis in Thematic Categories and Subcategories. The contents related the containing for physical and affective needs, characteristic of the roles incorporated by the woman in the division of work for gender, and the search of a reciprocity related to affection exchange, involving the caregiver and the cared person, were prevalent in the speech of the participants. The results point to the necessity of reintegration of the psychoafective balance of the woman, as domestic caregiver, in a context determined for the feminine vulnerability and the naturalization of the rules of gender.